SAT0387 Validation of Lupus Impact Tracker (LIT) in Five European Clinical Practice Settings. (9th June 2015) - Devilliers, H.; Mosca, M.; Schneider, M.; Pego-Reigosa, J.M.; Gunnarsson, I.; Maurel, F.; Garofano, A.M.; Perna, A.; Porcasi, R.
Abstract : Background: LIT is a disease impact tool that can be used longitudinally to focus on patient-centered concerns about the impact of systemic lupus erythematosus on patients' lives. Initially developed in the US and tested with patients in clinical settings. The results showed good acceptability, reliability and validity (1) . It needed to be tested in the real world in Europe by the physicians' community and demonstrate its validity for use. Objectives: To evaluate the cross-cultural validity of the Lupus Impact Tracker (LIT) in five European countries, and assess its acceptability and feasibility from both perspectives: patients and physicians. The secondary objective was to evaluate if using the LIT tool had any effect on communication between patients and physicians. Methods: This is a prospective, observational, cross-sectional and multicenter validation study conducted in clinical settings in five European countries (France, Germany, Italy, Spain and Sweden). Patients completed questionnaires before the visit: LIT, SF-36, Global Evaluation of Change (GEC) and care satisfaction. Physicians evaluated and reported during the visit flare occurrence, assessed disease activity using the Physician Global Assessment (PGA) and SELENA-SLEDAI tool (SS), and organ damage with the SLICC/ACR Damage Index (SDI). After the visit, both completed the LIT feedback questionnaire. Cross-cultural validity was assessed using the Differential Item Functioning (DIF) method. Results: 569 evaluable SLE patients were included by 25 specialists; outpatients: 91.7%, females: 89.9%, mean ± SD age: 43.5±13.0 years old, and mean ± SD SLE duration: 12.3±9.2 years. Patients presented with low/moderate disease: mean ± SD SS score was 3.4±4.5, mean ± SD SDI score was 0.8±1.4, and 18.3% of patients actually experienced flares. At inclusion, 37.6% were treated with corticosteroids + immunosuppressants in combination. The mean ± SD LIT score was 34.2±22.3, ranged from 0 to 100 (no lupus impact to impact of 100% of patient's daily life), and increased with SS and SDI scores. Patients found mainly that the LIT helped them to remember to discuss the impact of lupus has on their daily life (68.4%), to remember the specific ways lupus impacts their life (65.9%), and improved the communication with the physician (54.3%). Physicians would like to use the LIT with some particular patients (52.1%). The effect of LIT was related to many factors, e.g. age ≤45 years old (p=0.002) and low disease activity (no flares at visit, p=0.004). Nevertheless, completing LIT was sometimes perceived as a burden during their visit (16.8%) and not necessary with some patients (13.3%). Differences across countries were negligible (R 2 of 1-4%). Conclusions: The results showed the cross-cultural invariability, validity, reliability of LIT, its acceptance by both patients and physicians, and the feasibility of its use in routine clinical practice in the 5 countries. The physician intended to use the LIT mainly in specific situations and patients. References: Jolly M et al. Arthritis Care Res (Hoboken) 2014;66(10):1542-50. Acknowledgements: The study was funded by GlaxoSmithKline. Disclosure of Interest: H. Devilliers Grant/research support from: Study investigator, M. Mosca Grant/research support from: Study investigator, M. Schneider Grant/research support from: Study investigator, J. M. Pego-Reigosa Grant/research support from: Study investigator, I. Gunnarsson Grant/research support from: Study investigator, F. Maurel Consultant for: Study conduction, A. Garofano Consultant for: Study conduction, A. Perna Employee of: Employee of GSK, R. Porcasi Employee of: Employee of GSK